EFFECTIVENESS OF AQUAPARTBOX NATURAL SCIENCE IIC IN SUBSTANCE AND PARTICLE MODEL SUB MATERIAL CLASS 7 - Yohanes Advent Susprimadhi; Marisa Christina Tapilouw; Djohan Djohan (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2025)
Laboratory work by using laboratory equipment. It is important to develop simple and affordable laboratory equipment for learning natural science. It is expected that the learning laboratory work will increase from 15% to almost all learners achieve. Due to this condition, students could not understand the phenomenon of natural science. Therefore, the purpose of the research 1) to design a tool for laboratory work, AquapartBox IIC 2) to measure the chances of student achievement with interaction of AquapartBox IIC. IIC was developed using the ADDIE model development research method (Analyze, Design, Development, Implementation, and Evaluation). Based on the analysis, there is potential for developing natural science IIC instructional media. At the design stage, a sketch was produced which became the basis for the development of the IIC. At the development stage, the AquapartBox IIC and learning tools were validated and tested. The validators consist of a biology lecturer, a physics lecturer and a science teacher. At this stage students are given a pre-test and post-test. The pretest score obtained was 80.14 and the posttest score obtained was 87.6. This second value is included in calculating the NGain calculation, the N-Gain obtained is 0.38. Next, a final evaluation was carried out by teachers (4.15) and students (3.89) which showed that IIC was effective.